Information processing in healthcare at the start of the third millennium: potential and limitations - Haux, Reinhold; Knaup-Gregori, Petra; Bauer, Axel W.; Herzog, Wolfgang; Reinhardt, E.; Überla, Karl; Eimeren, Wilhelm van; Wahlster, Wolfgang (Methods of information in medicine, 2001)
The 21st century is said to be a century of the information society. We should be aware that continuing progress in information processing methodology (IPM) and information and communication technology (ICT) is changing our societies, including medicine and health care. At the start of the third Millennium we should ask ourselves, what progress can we expect from modern IPM/ICT for healthcare in the coming decade, what concerns does the information society have to face, and what steps have to be taken. These questions were addressed by clinicians, researchers and industrial representatives in a panel discussion at the joint conference ISCB-GMDS-99 of the International Society of Clinical Biostatistics and the German Society for Medical Informatics, Biometry and Epidemiology. Important aspects raised by the panelists and in the subsequent discussion were: (1) the main goal of expanding IPM/ICT should be to further improve quality of care, while maintaining reasonable costs; (2) with the support of modern IPM and ICT the boundaries between inpatient and outpatient care will fade away enabling a more efficient, patient-centered health care; (3) cooperation between health-care professionals will increase; there will be different ways of communication between them and with the patient, including modern ICT and the Internet; (4) society must be concerned with achieving equal opportunities in being informed about and in using new ICT; (5) misuse of data will remain a serious problem and can become an obstacle to progress.